Indirect pars repair for pediatric isthmic spondylolysis: a case series - Raudenbush, Brandon L.; Chambers, Reid C.; Silverstein, Michael P.; Goodwin, Ryan C. (Journal of Spine Surgery; Vol 3, No 3 (September 29, 2017): Journal of Spine Surgery, 2017)
Background: Isthmic spondylolysis (ISY) is a common cause of back pain in the pediatric population. Historically, non-operative treatments have had a very high success rate. The purpose of this study was to review the mid-term results of an indirect pars repair technique on reducing the visual analog score for pain (VAS), spondylolysis defect healing, complication rates and rates of return to pre-surgery activity level in pediatric patients who failed conservative care for ISY. Methods: A retrospective review of all pediatric patients (